What do we know about crop circles? - Hubbard, Ben, 1973- (What do we know about--? (Penguin Workshop (Firm)), 2022)
"Read about all of the rational and fanciful explanations for the flattened patterns in crops all over the world, from the United Kingdom to Australia. Artists and hoaxers alike have claimed credit for these massive projects, but some people think that the source could be paranormal. Are these circles an elaborate prank, or could they be something more?"--